EMOTIONAL AWARENESS IN ISLAM: STUDY OF THE QUR'AN, HADITH, AND NEUROSCIENCE - Syofrianisda Syofrianisda; Yondrizal Yondrizal; Rosniati Hakim; Dasrizal Dahlan; Ahmad Lahmi (Al-Irsyad: Journal of Education Science, 2025)
Emotional awareness is an individual's ability to consciously understand, recognize, and manage emotions. In Islam, the concept of emotional control receives significant attention, as reflected in the Quran and Hadith. This article aims to examine the alignment of Islamic teachings with modern neuroscience findings regarding the brain's mechanisms for processing emotions. A literature review approach was used to analyze Quranic verses, the Prophet's Hadith, and contemporary neuroscience research. The study's findings indicate that Islam not only regulates outward behavior but also encourages emotional control as part of worship and character building.